Cost-effectiveness of universally funding smoking cessation pharmacotherapy. Issue 2 (3rd April 2019) - Altman, Daniel; Clement, Fiona M.; Barnieh, Lianne; Manns, Braden; Penz, Erika
Abstract: RATIONALE: Tobacco use is the leading cause of preventable death in Canada and worldwide. Funding smoking cessation pharmacotherapy increases the likelihood of smoking cessation pharmacotherapy use, making a quit attempt, and the probability of abstinence from smoking. OBJECTIVES: The aim of our study was to model the cost-effectiveness of a health policy of funding smoking cessation pharmacotherapy for all Canadian smokers at no cost to the patient. METHODS: Using data from a Cochrane Review meta-analysis, a decision model incorporating utilization of smoking cessation products, quit rates, six-month continuous abstinence rates, relapse rate, and direct costs of smoking cessation pharmacotherapy and physician visits associated with full funding of smoking cessation pharmacotherapy for one quit attempt compared to no funding was constructed, and a sensitivity analysis was conducted incorporating variation in all inputs used. Our primary outcome was the incremental cost per life-year gained from universally funding smoking cessation pharmacotherapy compared to no funding for the average Canadian smoker. RESULTS: The average incremental cost per life-year gained of funding smoking cessation pharmacotherapy compared to no funding in the overall population was CaD$1030 (range CaD$250–10, 040) per life-year gained. In our cost-effectiveness analysis, the probability that universally funding smoking cessation pharmacotherapy is cost-effective is >95% at a willingness-to-pay threshold as low as CaD$10, 000 per life year gained. CONCLUSION: Universally funding smoking cessation pharmacotherapy appears cost-effective when compared to currently funded interventions in our healthcare system. Policy makers and government decision makers should fully fund smoking cessation pharmacotherapy for all Canadian smokers.